The influence of relationship quality on loyalty in service sector - Bojei, Jamil; Alwie, Aryaty (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
Stiff competition in the service market forces service firms looking for the best approach to attract and create a group of loyal customers. Relationship marketing is a strategy used by many service providers to maintain long-term relationship. Moreover, relationship quality is the manifest of successful relationship marketing activities. Good implementation of relationship marketing strategy can be seen from good relationship quality built between customer and service provider. The purpose of this research is to examine the relationship between relationship quality and loyalty across service types (Credence services versus Experience Services). In this study, relationship quality dimensions consist of interpersonal factors (closeness, communication, communication quality and special care) and firm factors (commitment, trust and satisfaction). The findings revealed that relationship quality influenced the loyalty in both service types. Importantly, all dimensions of relationship quality have different magnitude of influence on relationship quality in both credence services and experience services; with “commitment” has the strongest influence and “communication quality” as the weakest dimension. To sum up, in developing good relationship quality, the service provider should focus on both firm factors as well as interpersonal factors.